IMPACT OF CORPORATE GOVERNANCE ON FIRMS’ PERFORMANCE AND GENDER DIVERSITY WITH REFERENCE TO SELECT INDIAN AND OVERSEAS COMPANIES - Dr. Poornima Vijaykumar, Krithika J (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Corporate Governance refers to the structure and association that governs the corporate direction and firm’s performance. In short, Corporate Governance describes the firms’ responsibility towards the society. At present, the monitoring role performed by the Board is an important mechanism of Corporate Governance especially in the countries where external mechanisms are less developed. In the recent past, the selection of Board of Directors has become more gender balanced due to the existence of amended legislations, advocacy groups, and the institutional investors. There is a growing pressure to increase the gender diversity on the corporate board across the globe. The present study investigates the relationship and impact of corporate governance on firm’s performance and gender diversity. The study is descriptive in nature. The board gender diversity effect is not homogeneous as assumed in previous researches. To measure the effect in the present study, the researchers have employed a sample of 10 each Indian and Overseas Companies for the period ranging from 2009-2018. Using Regression – Ordinary Least Squares (OLS) as a method of estimation and Correlation analysis, the researchers observe the relationship between the variables used under the study. The study however indicates that there is no significant impact of Corporate Governance on ROA, ROE and gender diversity of the firms.